Irydocyklektomia z odwróconym płatem twardówki w czerniaku ciała rzęskowego - Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The aim was to present a case of ciliary body melanoma treated with block resection and scleral flap rotation. 49-year old woman with ciliary body melanoma and extrascleral extension appeared in our clinic. Block resection of ciliary body melanoma and scleral flap rotation was performed and additional ruthenium brachytherapy was applied. There was no complications during surgery and follow-up.